Preliminary data from a 4-year mirror-image and multicentre study of patients initiating paliperidone palmitate 6-monthly long-acting injectable antipsychotic: the Paliperidone 2 per Year study - Juan Antonio García-Carmona; Alba García-Pérez; Guillermo Isidro García; Luis Alberto Forcen-Muñoz; Santiago Ovejero García; Rocío Sáez Povedano; Ana Luisa González-Galdámez; Laura Mata Iturralde; Fernando Hernández-Sánchez; Mariluz Ramirez Bonilla; Paloma Fuentes-Pérez; Claudia Ovejas-Catalán; et al. (SAGE Publishing, 2023)
Background: Paliperidone palmitate 6-monthly (PP6M) is the first long-acting antipsychotic injectable (LAI) to allow for only two medication administrations per year, though there is presently limited insight into its effectiveness and potential added value in real clinical practice conditions. Objectives: To present our ongoing study and draw its preliminary data on patient characteristics initiating PP6M and adherence during the first year of treatment. Methods: The paliperidone 2 per year (P2Y) study is a 4-year, multicentre, prospective mirror-image pragmatic study taking place at over 20 different sites in Europe. The mirror period covers 2 years either side of the PP6M LAI initiation. Retrospective data for the previous 2 years are collected for each patient from the electronic health records. Prospective data are recorded at baseline, 6, 12, 18 and 24 months of drug administration and also cover information on concomitant psychiatric medication, relapses, hospital admissions, side effects, discontinuation and its reasons. Meanwhile, here we present preliminary data from the P2Y study at basal and 6-month period (first and second PP6M administration). Results: At the point of PP6M initiation, the most frequent diagnosis was schizophrenia (69%), the clinical global impression scale mean score was 3.5 (moderately markedly ill) and the rate of previous hospital admissions per patient and year was 0.21. PP6M was initiated after a median of 3-4 years on previous treatment: 146 (73%) from paliperidone palmitate 3-monthly, 37 (19%) from paliperidone palmitate 1-monthly and 17 (9%) from other antipsychotics. The mean dose of the first PP6M was 1098.9 mg. The retention rate at 6 months and 1 year of treatment on PP6M in our cohort was 94%. Conclusion: Patient and clinician preference for LAIs with longer dosing intervals was the main reason for PP6M initiation/switching resulting in high treatment persistence. Future data are needed to evaluate the full impact of PP6M in clinical practice.